Protective Effects of Orlistat on Lipid Profile, Cardiac Oxidative Stress Biomarkers and Histology in High-fat Diet-induced Obese Rats - ZA, Othman; WS, wan ghazali; L, Noordin; N, Omar; NA, Mohd. Yusof; M, Mohamaed (IIUM Medical Journal Malaysia, 2019)
Introduction: Orlistat is a widely used drug in treating obesity as it promotes weight reduction. The aim of this study was to determine the protective effects of orlistat (10 mg/kg/day) on cardiovascular parameters and oxidative stress biomarkers in high-fat diet (HFD)-induced obese rats. Methods: Twenty-four male rats Sprague Dawley rats were divided into three groups and fed with normal diet (N), HFD and HFD with orlistat (HFD+O). Orlistat was administered daily by oral gavage and after six weeks, all rats were sacrificed. Results: Administration of orlistat along with HFD (HFD+O) has brought significant decreases in Lee obesity index and LDL level compared to HFD group. Activities of cardiac superoxide dismutase (SOD), glutathione peroxidase (GPx) and catalase (CAT) were significantly higher, whereas level of oxidised LDL was significantly lower in HFD+O group compared to HFD group. HFD group had significantly higher necrotic patch area in myocardium while minimal histological changes were seen in HFD+O group. Conclusion: This study may suggest that administration of orlistat at 10 mg/kg/day for 6 weeks may have protective effects against the changes on Lee obesity index, lipid profiles, cardiac oxidative stress biomarkers and histology of myocardium in HFD-induced obese rats possibly through its hypolipidaemic and antioxidant actions.